S76 Tb Infection In The Nepali Population In South-east London Displays Different Characteristics Compared To The Tb Population In Nepal. (10th November 2014) - Dearnley, N; Eyres, R; Simpson, T; Stephenson, E; Belton, M; Palchaudhuri, P
Abstract : Introduction: The World Health Organisation classifies Nepal as having high Tuberculosis (TB) burden (Estimated incidence 163/100, 000). TB within the Nepali population in the UK has not been formally characterised but a recent study indicates unique characteristics compared to overall UK data. 1 These include higher rates of multi-drug resistant (MDR) TB (4.7% vs 1.6%), and lower rates of TB/HIV co-infection (1.1% vs 8%). We sought to investigate if these differences were also found in the TB population in Nepal or were unique to the immigrant population in SE London. Methods: Retrospective cohort analysis was performed of all Nepali TB patients in Greenwich between 2007–2012. Data collected included site, drug resistance, HIV co-infection and completion rates. Results were compared to Nepal National Tuberculosis Programme (NTP) data from 2012. Data analysis was conducted as part of an Internship with the Britain Nepal Medical Trust. Results: 86 UK patient records were analysed and compared to NTP 2012 data (n = 34, 245). TB patients in Greenwich were younger than patients in Nepal; 91.8% age <55 yrs compared with 72.5% of patients in Nepal. Of the patients diagnosed with pulmonary TB in Greenwich, only 19.7% had sputum smear positive disease, compared to 68% in Nepal. UK patients had higher rates of extrapulmonary disease compared to Nepal (41% vs. 23.8%). The rate of MDR TB in new diagnoses shows a marked difference; Greenwich having rates of 4.7% compared to 2.2% in Nepal. Despite the higher rates, risk factors for MDR TB were low in UK immigrants (HIV 1.1%, previous TB treatment 0% and MDR TB contact 0%). Treatment completion in Greenwich was 98% compared with 91% in Nepal, who run a national DOTS programme. Conclusion: Nepali expatriate TB patients display different characteristics to both UK and Nepal TB populations, and have high rates of MDR TB which cannot be accounted for by increased risk factors. Further studies are required to identify if this reflect differences in TB diagnostics or relate to the migration status of the Nepali patients. References: T Simpson, E Stephenson, P Palchaudhuri. A study of tuberculosis in an expatriate Nepalese community in South-East London. poster presentation. European Respiratory Society